Social Media Rebranding Strategies for Expanding Audience Reach on Higher Education Institution Promotions and Admissions - Ulfa, Marwa; Hariyati, Farida; Akbari, Deni Adha (Technium Social Sciences Journal, 2023)
This study investigates social media rebranding strategies for expanding audience reach in higher education institution promotions and admissions, focusing on computer-mediated communication (CMC) in private universities. UhamkaTV is a case study to understand CMC's role in adapting to the evolving social media environment. The research delves into rebranding efforts, including alterations in usernames, logos, and content types and their effect on audience engagement and reach. Emphasis is placed on the significance of ongoing analysis and evaluation to identify urgent concerns such as a decline in followers, interactions, and content reach. The results indicate that these efforts led to a more cohesive brand image, increased audience interaction, and improved promotion of academic programs. Furthermore, researchers found that effective internal communication and coordination are crucial for successfully implementing rebranding strategies. This study offers valuable insights for higher education institutions seeking to optimize their social media presence, drive admissions, and adapt to the rapidly changing digital landscape. By rebranding and diversifying content, institutions can enhance their audience reach and engagement, ultimately fostering growth in their admissions numbers.